The Role of Computer Aided Diagnosis (CAD) in Medical Imaging - Shin, Seung Won; Kim, Kwang Gi (Central Asian Journal of Medical Sciences, 2015)
Objectives: We introduce the various methods of image analysis used for CAD. In addition, we provide a guide for the clinician through examples which use the CAD. Methods: Medical images consist of individual pixel elements, to which discrete brightness or color values are assigned. Various methods have been utilized for the analysis of these images. We introduce the five methods: shape analysis, texture analysis, parametric mapping analysis, classification methods and segmentation methods. Results: Various image analysis techniques used in the CAD are quantified by analyzing the various features of the lesion shown in the image. It is used as a process for deriving the best diagnosis for the disease through the comparison of the existing data. It proposes an example of a CAD system being studied using a variety of image analysis techniques. Conclusion: Nowadays, medical imaging has improved to show the functional state of the inner body. Furthermore, accelerated advances in computer-based technology have widely enlarged efficiency of saving, transmission and analysis. Improvement of CAD will expand the utilization range of CAD in 2D and 3D medical imaging. Also, we expect that CAD system will evolve the automatic diagnosis support system.